TAXES AND THEIR ROLE IN ENHANCING THE STATE’S GENERAL BUDGET REVENUES - Assistant Lecturer. Hanan Jumaa Hanzal (American Journals, 2024)
Tax is one of the important means of achieving financial stability and financing the state’s general budget. The importance of taxes has increased in recent decades as they represent one of the tools of financial policy. Interest in taxes is increasing for various countries not only because they are the main source of public revenues, but also for considerations, the most important of which are the economic policy tools used. In directing economic activity and influencing it, it is also considered a means to satisfy public needs, as it exercises multiple economic, social, cultural and service functions to influence economic life. The tax collection in Iraq faces major challenges, including that the financing revenue from taxes in Iraq is weak and has no importance in the budget, even after the decline in oil prices in global markets, and did not contribute to the basis of financing the state’s general budget. The research is based on the hypothesis to prove that the financing proceeds of taxes can be an important resource that enables them to diversify sources of income and have a positive role in financing the general budget, as taxes are of great importance in supplying the state budget with the financial resource that contributes to enhancing the budget’s ability to face the financial burdens that are It is obligated to perform it towards members of society based on the state’s responsibility to intervene in the economic, social and political aspects of its citizens. Based on the importance of the role of taxes in our present time, as they are an important source for the state that cannot be dispensed with, despite the presence of the main source of public revenues in the state, which is oil, so the research addresses the importance of adopting taxes in financing the state’s general budget in financing its various revenues, even if that is a small percentage. The total diverse tax revenues in Iraq constitute a significant revenue for the state. The research came out with several conclusions, the most important of which is tax revenues, which are considered one of the important sources in financing the general budget in most countries of the world, as well as achieving political, economic and social goals. Also, the reality of the general budget in Iraq and the extent of the contribution of tax revenues through the sources that we relied on, we see that taxes in Iraq have been characterized by their weak impact on financing the general budget due to the budget’s reliance mainly on oil revenues. Based on this, several recommendations have been identified, the most important of which is the need to work on Activating the role of taxes in financing the state’s general budget by carrying out serious reforms in the tax system by reviewing the tax laws. There is a need to carry out real reforms in the Iraqi tax system and advance it to the level that achieves the objectives required of it, foremost of which is the financing goal of the budget. There must also be openness to the experiences of advanced tax systems and benefiting from them in various areas of work
Keywords: Taxes, revenues, general budget